The Effectiveness of Using Interactive Video in Teaching Arabic Calligraphy / فعالية استخدام الفيديو التفاعلي في تعليم الخط العربي - Muhammad Afif Amrulloh; Ahmad Basyori (Abjadia, 2019)
The interactive video from the modern trends of education technology as the most important and latest tools of education. And can be used as a means to teach any material of the Arabic language at the university, including Arabic calligraphy. In the Department of Islamic Education Department at Radin Intan Islamic State University Lampung teaches Arabic calligraphy to students in the fourth grade in terms of the subject matter. The Arabic calligraphy teacher is sometimes taught using the chalkboard in his teaching, as well as using the technology like Fur Fuen and we do not use interactive video in his education. The aim of this research is to find out the effectiveness of using interactive video in teaching Arabic calligraphy to students of this university. This research used the experimental approach in the design of both groups and quantitative input. The data taken by the author in this study are the result of the tribal and post-test of the two groups. As a result of the equation (70,70), that is, on the "good" score, which the students obtained higher and higher than the standard result (70.00), which the writer decided to indicate that this video is effective. (57.56) and post-test (70.70). The result of the difference between them (13,14) indicates that the video method has an effective degree. In other words, the use of interactive video fundamentally affects the improvement of student writing